2020
DOI: 10.1155/2020/7141237
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model and Experimental Study on Braking Distance under Emergency Braking with Heavy Load of Escalator

Abstract: In order to study the relationship between the braking distance and the load of escalator and realize the prediction of the rated load braking distance with a little load, the method of combining theoretical analysis and experimental research is used. First, the dynamic characteristics of the escalator during emergency braking are analyzed, and the prediction model of the braking distance of the escalator under different loads is derived based on the law of conservation of energy. Furthermore, the influence co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Equation (2) shows the total kinetic energy of the system represented by Fig. 1, as the sum of the kinetic energies of the suspension systems, right and left, and the kinetic energy of the elevator cabin [12].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (2) shows the total kinetic energy of the system represented by Fig. 1, as the sum of the kinetic energies of the suspension systems, right and left, and the kinetic energy of the elevator cabin [12].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In [11][12][13][14][15][16], studies are presented that revealed that vibration during the elevator emergency braking process directly affects the performance of the elevator traction system, thus affecting the safety, reliability, and comfort of passengers. In [17], results are presented that demonstrate that the vertical vibrations of the elevator traction system are maximized during the braking operation.…”
Section: Introductionmentioning
confidence: 99%
“…References [5][6][7][8][9] studied the braking distance of escalators. Jiang et al 5 designed a wireless monitoring system,which can replace the backward manual measurement method for braking distance.…”
Section: State-of-the-art Researchmentioning
confidence: 99%
“…Liu 8 analyzed the calculation of the escalator braking distance by its established calculation formulas, which can provide theoretical basis for reference. Li et al 9 studied the relationship between the braking distance and the load of escalator, realized the prediction of the braking distance with little load. Reference [10][11][12][13][14] studied the braking performance.…”
Section: State-of-the-art Researchmentioning
confidence: 99%
“…Modern hardware for information processing and control solution implementation is considered in 15 17 . These studies focused on tracking moving objects, posturing people, and predicting emergency braking on escalators.…”
Section: Introductionmentioning
confidence: 99%